Gender Differences in Moral Development in Online Comments About Infidelity on TikTok - Zalukhu, Irfan; Hamzah, Hamzah (English Language and Literature, 2023)
The research analyzed whether there were differences in the level of moral development of TikTok users when infidelity occurred based on commenter gender. The method for this research was descriptive-qualitative. This research used this method to analyze moral development based on gender's comments on TikTok about infidelity. The source of data for this research was the comments that had been taken from several videos of infidelity on TikTok. The data for the research problem were comments containing moral development. The findings reveal that male and female commenters participate in conventional moral development with comparable tendencies.